Therapeutic inhibition of apoC-III for the treatment of hypertriglyceridemia. (April 2015) - Bell, Thomas A; Graham, Mark J; Baker, Brenda F; Crooke, Rosanne M
Hypertriglyceridemia is a common feature of many metabolic disorders and has been identified as risk factor for cardiovascular disease. ApoC-III is commonly associated with triglyceride rich lipoproteins and has been identified as a potent modulator of plasma TG levels. The purpose of this review is to provide background on apoC-III and its role in the regulation of plasma TG and lipoprotein metabolism and to highlight preclinical and genetic evidence supporting apoC-III as a central target in cardiovascular disease progression. Finally, recent results from clinical trials evaluating a second generation antisense oligonucleotide (ASO) inhibitor of apoC-III will be summarized and the potential impact such a drug could have in the treatment of hypertriglyceridemia and associated comorbidities will be highlighted.